An estimate of anthropogenic heat emissions in China. (19th July 2015) - Lu, Yan; Wang, Qin'geng; Zhang, Yanyan; Sun, Ping; Qian, Yu
ABSTRACT: Anthropogenic heat emissions (AHEs) are a contributor to global climate change and may affect the climate and air quality in many ways. To gain a complete picture of AHEs in mainland China and to lay the groundwork for modelling of regional climate and the environment, AHEs from energy consumption and human metabolism were estimated, and an inventory was established with gridded distributions and profiles of temporal variations. This was based on the top–down inventory approach by using officially published statistical data. Results indicated that total AHE of the mainland was 1.2 × 10 20  J·a −1, of which industry, transportation, buildings and human metabolism contributed 73.0, 11.6, 10.6 and 4.8%, respectively. Coal and electricity accounted for approximately 74% of the total emissions from energy consumption. The annual average heat flux of the mainland was 0.4 W·m −2, with a sharp difference between the eastern and western regions. Fluxes in the eastern regions were mostly between 0.5 and 20 W·m −2, and they were between 0 and 0.05 W·m −2 in the western regions. In urban or built‐up areas of typical cities, the heat fluxes may be much higher than the average for larger areas, typically ranging from 20 to 100 W·m −2 . Region‐specific profiles of temporal variations will improve the inventory in the future, which can be applied to climatic and environmental models to obtain in‐depth knowledge of the effects of AHEs.